INTEGRASI NILAI EKONOMI ISLAM UMER CHAPRA DALAM KEBIJAKAN PEREKONOMIAN INDONESIA - Anisa, Lina Nur (Fakultas Ekonomi Bisnis Islam, 2024)
The integration of Umer Chapra's Islamic economic values into Indonesia's economic policies presents a compelling vision for achieving economic justice, social welfare, and equitable wealth distribution. The aim of this research is to elucidate the main concepts within Chapra's economic thought and analyze the opportunities and challenges associated with integrating these values into Indonesia's economic policies. The research employs a qualitative approach, utilizing literature review and policy analysis. This study involves reviewing books, journal articles, policy documents, and official reports relevant to Islamic economics and Indonesian economic policies. The findings indicate that implementing Chapra's principles through fiscal and monetary policies can significantly enhance economic stability and growth. Successful examples include the use of zakat in Malaysia as a fiscal policy tool for poverty alleviation and the adoption of Shariah-compliant financial products in Saudi Arabia, contributing to economic diversification. Additionally, Islamic values-based economic empowerment programs in Indonesia, such as those implemented by BAZNAS and Dompet Dhuafa, show significant improvements in community welfare, including poverty reduction, increased income levels, and better access to education and healthcare. However, the research also identifies challenges such as efficient and transparent management of zakat funds, increasing public awareness, and expanding the reach of programs to remote areas. Integrating Umer Chapra's Islamic economic values into Indonesia's economic policies can create a more just, inclusive, and sustainable economic system. This research recommends that the government and policymakers strengthen regulatory frameworks, enhance public education, develop innovative financial products, and ensure transparency and accountability in program implementation.